EFFECT OF LEARNING MODEL TYPE QUIZ TEAM ON STUDENT LEARNING OUTCOMES IN PRODUCTIVE SUBJECT MATERIAL HORIZONTAL POSITION MEASUREMENT TECHNIQUE GRADE XI MAPPING SURVEY AT SMKN – 1 PALANGKA RAYA ACADEMIC YEAR 2014/2015 - Melda Wati; Sitinjak, Tarita Aprilani (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2015)
The research was conducted in Grade XI Engineering Mapping Survey SMK Negeri 1 Palangkaraya which consists of one class which amounts to 28, then the class is divided into two classes, namely class experimental and control class, for the experimental class there are 15 students who are further subdivided into three teams, namely team A , B and C in each team there are 5 students and a control class numbered 13 students. The result of this research can be seen in the results of the hypothesis test where tcalc = 3.41 > 2.04 (ttable). For experimental class the highest score is 92 and the lowest is 68 with an average score of 80, while the highest score in control class is 85 and the lowest score is 46 with an average score of 65.5. It can be deduced that learning using learning model Type Quiz Team can improve student learning outcomes in subject: a horizontal position measurement of material in the XI Engineering Surveying Mapping Palangkaraya SMK Negeri 1 academic year 2014/2015 . To the teachers or instructors to choose teaching model Type Quiz Team, especially in subject a horizontal position measurement materials for learning, model Quiz mode is pretty good way in improving student learning outcomes.